Class, Power, and Social Change: A New Historicist Approach to August Strindberg’s Miss Julie and Anton Chekhov’s The Cherry Orchard - Salam el Baba; Lutfi Hamadi (European Scientific Journal, ESJ, 2024)
This paper conducts a new historicist analysis of Strindberg’s Miss Julie (2008) and Chekhov’s The Cherry Orchard (1951), exploring how these plays reflect and respond to the social, political, and cultural dynamics of the late nineteenth and early twentieth centuries. By examining the interaction between literature and history, this study reveals how these works depict the tensions between old and new social orders, the shift of power dynamics, and the struggles of individuals caught in the midst of profound societal changes. Although both classic works have been the subject of a lot of critical studies, neither has been studied from a new historicist perspective. The shift in power dynamics at the very beginning of the twentieth century with the deterioration of the aristocratic sovereignty and the rise of the middle class is a prominent theme in both plays. This shift conveys the inevitability of change that disrupts routines, norms, and tradition. From a new historicist perspective, those who are marginalized do not necessarily match readers’ initial assumptions, as the measures used to exhume the stigmatized characters are never the same as those utilized in other theoretical frameworks. It is not a battle between two antagonistic groups; nor is it a Greek tragedy that instigates catharsis upon the heroes’ tragic falls, simply because there is no hero, only an antihero. While Strindberg focuses on the changing role of women and the emergence of feminism in addition to class struggle, a new historicist approach reads these radical social, political, and economic changes as a result of historical changes taking place in Europe during that era. Chekhov, in turn, depicts the historical fall of aristocrats who had started to lose power on behalf of wild capitalism during the same era.